Climate change education and research: possibilities and potentials versus problems and perils?. Issue 6 (3rd June 2019) - Reid, Alan
Abstract: This article introduces key features to the background, themes and implications of three collections available in Environmental Education Research that focus on climate change education and research. The problems and perils of scholarship and inquiry in this area are highlighted by contrasting these with some of the possibilities and potentials from a broad range of studies published in this and related fields of study, for example, in understanding who is doing the teaching and learning in climate change education, and in identifying the conceptual, policy and economic drivers and barriers related to its uptake. Key points for debate and action are identified, including for so-called 'pyro-pedagogies' and 'practice architectures', and the various philosophical, political and phenomenal aspects of climate change education that are likely to affect its prospects, at this moment and into the immediate future.